Perluasan Pasar Batik Berorentasi Export Melalui Pewarna Alam Di Kota Jepara - Widagdo, Jati; Bagas Yuliawan, Ahmad (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Indonesian batik has been designated as one of the world's cultural heritages by the United Nations (UN) under the United Nations Education (UNESCO). Batik owned by the Indonesian people was originally only found on the island of Java, but now it has developed and spread throughout Indonesia, with different characters in each region. This study uses a qualitative study with field studies and observations. If we look at the technique of making batik, it is divided into two, namely batik with a writing technique and batik with a stamping technique. Batik products that use factory-made (synthetic) colors may not be exported to the Netherlands. The same decision is also used by countries such as America, Germany, Malaysia, however, batik is also becoming increasingly global and foreign consumers prefer natural colors even though they have a price. which is more expensive, but has its own characteristics so that consumers are more interested in natural dyes and ignore the high price. This research aims to examine and explore the use of natural dyes in the process of making Jeapara batik, this is due to the natural wealth in Indonesia and is able to provide significant benefits for craftsmen. Through this research, it is hoped that it can become a reference for craftsmen to use natural materials as the main component of batik coloring.